In vitro phosphorylation of purified tobacco‐leaf phosphoenolpyruvate carboxylase - Wang, Yue-Hao; Chollet, Raymond (FEBS letters, 1993)
C3‐leaf phosphoenolpyruvate (PEP) carboxylase (PEPC) was purified about 1,000‐fold from tobacco and displayed a final specific activity of 35 μmol/min/mg protein, an apparent K m (total PEP) of 95 mM (both at (pH 8.0, 30°C), and an I50(l‐malate) value of 0.14 mM at pH 7.3, 0.2 mM PEP. The rapid, 5‐step protocol involved polyethylene glycol fractionation and sequential FPLC on hydroxylapatite, phenyl‐Sepharose, Mono Q and Superose 12. The electrophoretically pure protein and purified C4‐leaf PEPC were phosphorylated in vitro in a reconstituted system with PEPC‐kinase isolated from illuminated tobacco and maize leaves. These reciprocal phosphorylation experiments (i) indicate that Ser11 of tobacco PEPC is the likely target residue, situated in the plant‐invariant Glu/Asp‐Lys/Arg‐X‐X‐Ser phosphorylation motif near the N‐terminus, and (ii) lend support to the recent hypothesis that C3‐leaf PEPC is subject to regulatory phosphorylation in vivo.